Snow Sports Trauma and Safety 2017
DOI: 10.1007/978-3-319-52755-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Release of Ski Bindings: A Sex Comparison

Abstract: Background: Among recreational skiers, ACL injury risk is about three times greater in females compared to males and female skiers suffering from ACL injury reported about 20% points more frequently a failure of binding to release compared to male skiers with an ACL injury. Performing a daily self-release test of ski bindings, however, can prevent skiing-related injuries of the lower extremity.Aim: To evaluate to what extent uninjured male and female skiers are able to selfrelease their ski bindings which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
0
16
3
Order By: Relevance
“…After performing a standardized warming up program on a stationary cycle ergometer, the maximal isometric leg strength of both legs was tested by isometric leg strength test. Afterward, the self-release test of ski bindings was conducted in accordance with the methods described by Posch et al 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After performing a standardized warming up program on a stationary cycle ergometer, the maximal isometric leg strength of both legs was tested by isometric leg strength test. Afterward, the self-release test of ski bindings was conducted in accordance with the methods described by Posch et al 15 …”
Section: Methodsmentioning
confidence: 99%
“… 15 In a recent study among 30 physically active young adults with a self-reported advanced skiing skill level, Posch et al 15 clearly showed that more females than males were unable to self-release their ski bindings within the self-release test (80% vs 27%, p <0.01) at least once with both legs, although all bindings were correctly adjusted according to the International Standards Organization (ISO) 11088 standard for binding setting values using an electronic test device and sexes did not differ regarding the relative isometric leg strength. In addition, the study by Posch et al 15 also revealed a 20% difference of measured relative release torques (RRT) among trials of failure of binding release between the two sexes (males 50.6%±20.1%, females 40.9%±20.2%, p =0.009), characterizing a huge difference to the recommended ISO 11088 binding setting values. LaPorte et al 16 already demonstrated that lowering binding release values by 15% among female recreational skiers could reduce knee injuries without an increase of inadvertent releases.…”
Section: Introductionmentioning
confidence: 99%
“…The same applies to other causes of accidents on backcountry tours such as falls or getting lost in foggy conditions, which should also be less common due to technical developments such as GPS (Global Positioning System), making orientation easier. Furthermore, the extreme development of the ski-shoe-binding unit for backcountry skis should also result in lower injury rates [3,27,28]. Nowadays, modern plate bindings of backcountry skis have a safety mechanism that has been present in alpine skiing for years [3,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the extreme development of the ski-shoe-binding unit for backcountry skis should also result in lower injury rates [3,27,28]. Nowadays, modern plate bindings of backcountry skis have a safety mechanism that has been present in alpine skiing for years [3,27,28]. The modern pin bindings of backcountry skis with inserts in the front of the shoe also have a security mechanism [3,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation